1962
DOI: 10.1126/science.137.3529.541
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic Antagonists as Analgesics

Abstract: 2-Dimethylallyl- 5,9-dimethyl-2'-hydroxybenzomorphan (Win 20,228) was found to be a weak antagonist of morphine and meperidine, whereas 2-allyl-5-ethyl-2'- hydroxy-9-methyl-6,7-benzomorphan (Win 19,362) and 2-allyl-2'-hydroxy-5,9- dimethyl-6,7-benzomorphan (Win 19,631) were about three times as potent as nalorphine. Preliminary clinical trials indicate that Win 19,362 is about twice as potent as morphine as an analgesic but, like nalorphine, is capable of producing severe psychic side effects. Win 20,228 is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Postoperative patients treated with N -allylnormetazocine (NANM, SKF-10,047) experienced profound hallucinogenic and dysphoric effects (Keats and Telford, 1964). Similar effects are induced by other benzomorphans, including pentazocine and cyclazocine (Archer et al, 1962; Lasagna et al, 1964; Haertzen, 1970; Beaver and Feise, 1977; Coursey, 1978; Kumor et al, 1986). …”
Section: Introductionmentioning
confidence: 84%
“…Postoperative patients treated with N -allylnormetazocine (NANM, SKF-10,047) experienced profound hallucinogenic and dysphoric effects (Keats and Telford, 1964). Similar effects are induced by other benzomorphans, including pentazocine and cyclazocine (Archer et al, 1962; Lasagna et al, 1964; Haertzen, 1970; Beaver and Feise, 1977; Coursey, 1978; Kumor et al, 1986). …”
Section: Introductionmentioning
confidence: 84%
“…7). Thus, it was revealed that a dose of s.c. pentazocine not more than 20 (20)(21)(22)(23)(24)(25).…”
Section: Methodsmentioning
confidence: 99%
“…Pen tazocine, (2a,6a,ll R* ) -( f )-1,2,3,4,5,6-hexahydro-6,11-dimethyl-3-(3-methyl-2-butenyl) -2,6-methano-3-benzazocin-8-01' (Ia), is a member of the benzomorphan series of compounds (1). Pentazocine is a potent, analgesic and a weak narcotic antagonist, possessing little dependence potential (2).…”
mentioning
confidence: 99%